Using the Uganda Demographic and Health Surveys from 2011 and 2016 to assess changes in Saving Mothers, Giving Life intervention districts - Lindsay Mallick; Trinadh Dontamsetti; Thomas Pullum; Julia Fleuret (Journal of Global Health Reports)
# Background